O (re)conhecimento do lazer em brinquedoteca hospitalares - Tonia Lopes Soares Mol (2010)
The Toy Library Hospital configure themselves today within the health institutions while the children play areas aimed at recovery. However, currently, has turned a new look to this space, increasing its importance in the context of health. From these considerations, the objective of this study was to detect and analyze the reality of toy Hospital Units in the public network of the city of Belo Horizonte - MG, in order to achieve a diagnosis of the situation of care for hospital playrooms, to identify the individuals responsible for toy library hospital in health care facilities, identifying projects, programs that are linked to those spaces within the hospital, identifying the concepts of leisure and hospital humanization of the professionals present at the speech of those institutions, and to check whether there are public, private and / or philanthropic directed to these spaces. The rationale of this study is based on the search for the expansion of knowledge about Toy Library Hospital and understanding of their relationship with the discussions about the humanization of the hospital and leisure. The work was structured in three parts. The first deals with the debate on the humanization, reconciled to the issue of health in a larger view. The second part deals with the contextualization of the discussion of toy library in its history and trajectory, as well as roles, goals and ratings. And finally, we present the analysis made from the institutions surveyed, rising to the points that were recurrent and the divergent issues. As methodological possibilities, this study combines literature search, along with field research. Field research was carried out using the technique of semi-structured interviews with the coordinators / directors of the space and allowed us to understand fundamental questions about the area studied. From this analysis, we observed that the idea that builds on the toy library hospital has advanced in recent years and now constitutes much more than concrete evidence, such as physical spaces and toys. Understanding leisure relates this dimension of culture, especially the idea of occupation of idle time and lowering stress and anxiety related to hospital procedures. However, it is possible to see visions that relate to the development of leisure subjects and the educational processes that are part of involvement in these actions. Regarding the concept of leisure, this action is restricted to the prospect of playing, but this is the idea that leisure is a possibility of work that helps in completion of the proposed hospital humanization. And health care professionals recognize the importance of multiprofessional work, seeking to consolidate an interdisciplinary approach, so there is a unique professional training. About the projects and actions developed in the toy library hospital. These spaces are often "self-sustaining" for not having money specifically targeted, it is necessary to mobilize to develop partnerships, projects and links to other organs. General consensus is that these spaces are understood as a way to enhance the humanization.